VoiceStick / Nurul Dania Fatihah Jamalulail … [et al.] - Jamalulail, Nurul Dania Fatihah; Azman, Nur Syaierah; Affian, Nurasfarina; Sani, Nor Allys Athiyah; Ronny Izwan, Aleya Natasha; Mohd Ariffin, Arissa Husna; Othman, Hamizah (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2024)
Each day, advancements in technology continue to improve, leading to the development of numerous innovative concepts catering to a diverse audience. Braille remains the prevailing standard for assisting special need individuals. Regrettably, the process of converting writing into braille incurs significant costs and demands a substantial amount of time. The VoiceStick is a sophisticated optical character recognition device that we have developed specifically to enable visually impaired individuals to access any book. The VoiceStick combines voice-output technology with scanning technology to enable blind or dyslexic individuals to read written text, like normal sighted individuals. In summary, when we utilise the VoiceStick to scan a page, the selected language is used to audibly read the text. The objective is to aid individuals who experience visual impairments and dyslexia. Users can increase the loudness of their VoiceStick by connecting to a speaker. VoiceStick provide consumers with a personalised experience by letting them to change the settings, preferences, and orders according to their needs and preferences. The objective of developing this device was to address the concerns identified by the World Health Organisation (WHO), which reports a worldwide population of 314 million individuals with visual impairments, including 45 million who are completely blind.